PENGARUH LAMANYA WAKTU PERENDAMAN BENIH SAWI DENGAN PGPR (PLANT GROWTHPROMOTING RHIZOBACTERIA) DAN DOSIS PUPUK ORGANIK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SAWI (BRASSICA JUNCEA L.) - Kuspianto, I Wayan Seputra; Widnyana, Ketut; Sapanca, Putu Lasmi Yuliyanthi (Agrimeta: Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2017)
The purpose of this research is to know the influence of the treatment soaking seed mustard greens with PGPR and dosage of organic fertilizer against growth and crop mustard greens.The research was carried out in pots at the Subak Gangsang, the village of  Marga Dajan Puri, Sub-district, Tabanan Regency, which lasted for 35 days calculated from the time of planting 15 August up to harvest 20 September 2016.The research of using random Random Draft Basic Design Group (RAK) factorial with three replicates. It's entirely contained 36 pot experiment.The results of the analysis of the statistics show that of the 12 treatment interaction between treatment soaking seed mustard greens with PGPR and dosage of organic fertilizer against growth and crop mustard greens (WxD) give different very real influence (P < 0.01) for most of the observed parameters, except against the parameters of plant root length-1 giving different influences isn't real (P 0.05 >). The duration of time of soaking of seed mustard greens with PGPR (W) gave significant effect (P <0,05) to very real (P <0,01) to most observed parameters, except for maximum plant height parameters, dry weight of root oven -1, dry weight of oven-economical plant-1, and economical wet weight of acre -1 which gives no significant effect (P> 0.05). The treatment of organic fertilizer dosage (D) gave no significant effect (P <0.05) on most parameters observed, except for the wet-root weight parameter of plant-1 which gave a very real effect (P <0.01)